Basic Research of Plasmodium vivax Biology Enabling Its Management as a Clinical and Public Health Problem - Baird, J. Kevin (Frontiers in Cellular and Infection Microbiology, 2021)
The emerging understanding of Plasmodium vivax as an infection seated in extravascular spaces of its human host carries fundamentally important implications for its management as a complex clinical and public health problem. This progress begins to reverse decades of neglected research borne of the false dogma of P. vivax as an intrinsically benign and inconsequential parasite. This Review provides real world context for the on-going laboratory explorations of the molecular and cellular events in the life of this parasite. Chemotherapies against the latent reservoir impose extraordinarily complex and difficult problems of science and medicine, but great strides in studies of the biology of hepatic P. vivax promise solutions. Fundamental assumptions regarding the interpretation of parasitaemia in epidemiology, clinical medicine, and public health are being revisited and reassessed in light of new studies of P. vivax cellular/molecular biology and pathogenesis. By examining these long overlooked complexities of P. vivax malaria, we open multiple new avenues to vaccination, chemoprevention, countermeasures against transmission, epidemiology, diagnosis, chemotherapy, and clinical management. This Review expresses how clarity of vision of biology and pathogenesis may rationally and radically transform the multiple means by which we may combat this insidiously harmful infection.